Are within and/or between session improvements in pain and function prognostic of medium and long-term improvements in musculoskeletal problems? A systematic review. (February 2020) - Runge, Nils; Aina, Alessandro; May, Stephen
Abstract: Background: Initial or between session improvements in pain and/or function are often considered to be predictive of ultimate outcomes in musculoskeletal problems. Objective: To determine the long-term prognostic value of within and between session improvements to pain and function. Design: Systematic review of relevant literature. Method: A search was made of multiple databases (Pubmed/Medline, Cochrane, Cinahl, and AMed) using relevant search terms. Titles, abstracts, and then full texts were filtered to find articles that met the strict inclusion/exclusion criteria. Searching, data extraction, and quality assessment, using GRADE, were done independently by two authors. Disagreements were resolved by consensus. Results: Only 13 articles met the criteria for inclusion. For the effect of pain location or pain intensity changes in the first treatment session on medium or long-term pain, disability, return-to-work, or global outcomes nine outcomes were available. Findings were mostly inconclusive (5) or negative (3). There was only one study evaluating between session improvements with ambiguous results. There were no studies evaluating the prognostic value of early improvements in function. Conclusions: There is no conclusive evidence to support the concept that early changes in pain location or pain intensity offer a good longer-term prognosis on a variety of outcomes; and no evidence relating to early improvements in function. The idea that patients who appear to improve in the first treatment session will do well longer term is not supported by the literature. Highlights: Within and between session changes are thought to be good prognostic factors. This systematic review identified 13 studies that investigated this association. The evidence for changes in pain location as a prognostic factor was inconclusive. No evidence for within session changes in pain intensity as prognostic factor. Very limited evidence for prognostic value of between-session changes on disability.